The Ageing Immune System and Health - Bueno, Valquiria; Lord, Janet M.; Jackson, Thomas A. (Springer International Publishing : Imprint: Springer, 2017)
The present book intends to provide an update on immunosenescence and how deficiencies in the immune system contribute to a higher susceptibility to infections, decline in organ function, reduced vaccination responses, age-related disease and the ageing process itself, negatively affecting longevity. Our focus is on the main changes in immune system cells and their products occurring during the ageing process and the possible consequences for health and disease. This includes: discussion of the modulatory and/or suppressive mechanisms associated with the alterations in T regulatory cells, B regulatory cells and Myeloid Derived Suppressor cells; changes in the immune system observed in chronic neurodegenerative diseases, cancer, lung disease and frailty will also be discussed. Most importantly we provide recent literature information about possible interventions (focusing on physical activity) that could alleviate the negative effects of immunosenescence. The Ageing Immune System and Health is a comprehensive guide on the field intended to all physicians, researchers, professors and students interested on relationship between immune system, ageing and health. .